Develop the concept of sustainable residential college: study a room space - Buyung, Mohd Reduan; Shafii, Haryati; Yusoff, Noor Ain; Buyung, Nurul Rezuana (Science Publishing Corporation, 2018)
Developing the concept of a sustainable residential home concept requires room space study. Discomfort residents living in public college residences contribute to the implementation of this study. The result of adverse impact on the learning process of the population has continued to affect the sustainability of residential colleges. This problem eventually leads to the deterioration of the quality of life of its inhabitants. The purpose of this study is to identify the degree of comfort of accommodation space as the main hall in the public university residential college by using quantitative methods. The study took seven public university residential colleges from USM, UPM, UTHM, UITM, UTEM, UPSI and UKM (2874 respondents) into account. Software Statistical Package for the Social Sciences (SPSS) software has been used to analyze descriptive and inferential data The results of the study show that the comfort of the occupants in the room space facilities is at a comfortable level.. T test showed that female respondents have a higher level of comfort. For the T test, there is a weak positive relationship between the years of occupation and the year living in residential college with the comfort of the room facility. The level of comfort of a residential college is important as it is able to affect the overall quality of life of the occupants. The result of this assessment served as a basis to identify the level of comfort that was assessed by the occupants in regards to the condition of the room. Therefore, the information acquired from this study can contribute to the development of a sustainable residential college to make them more comfortable and conducive in the future.